Bur1 functions with TORC1 for vacuole‐mediated cell cycle progression. (15th February 2022) - Jin, Yui; Jin, Natsuko; Oikawa, Yu; Benyair, Ron; Koizumi, Michiko; Wilson, Thomas E; Ohsumi, Yoshinori; Weisman, Lois S
Abstract: The vacuole/lysosome plays essential roles in the growth and proliferation of many eukaryotic cells via the activation of target of rapamycin complex 1 (TORC1). Moreover, the yeast vacuole/lysosome is necessary for progression of the cell division cycle, in part via signaling through the TORC1 pathway. Here, we show that an essential cyclin‐dependent kinase, Bur1, plays a critical role in cell cycle progression in cooperation with TORC1. A mutation in BUR1 combined with a defect in vacuole inheritance shows a synthetic growth defect. Importantly, the double mutant, as well as a bur1‐267 mutant on its own, has a severe defect in cell cycle progression from G1 phase. In further support that BUR1 functions with TORC1, mutation of bur1 alone results in high sensitivity to rapamycin, a TORC1 inhibitor. Mechanistic insight for Bur1 function comes from the findings that Bur1 directly phosphorylates Sch9, a target of TORC1, and that both Bur1 and TORC1 are required for the activation of Sch9. Together, these discoveries suggest that multiple signals converge on Sch9 to promote cell cycle progression. Synopsis: The yeast vacuole is required for cell cycle progression through early G1 phase via TORC1 signaling. This study reveals that Bur1/Cdk9, a cyclin‐dependent kinase, is also required for vacuole‐mediated cell cycle progression and acts in parallel with TORC1. Bur1/Cdk9 is required for cell cycle progression through G1 phase. Bur1 functions in parallel with TORC1 through direct phosphorylation of Sch9. TORC1 and Bur1 each phosphorylate unique sites on Sch9, and in addition phosphorylate sites in common. Abstract : The yeast vacuole is required for cell cycle progression through early G1 phase via TORC1 signaling. This study reveals that Bur1/Cdk9, a cyclin‐dependent kinase, is also required for vacuole‐mediated cell cycle progression and acts in parallel with TORC1.